Dalhuisen on transnational and comparative commercial, financial and trade law. Volume 4, Transnational movable property law - Dalhuisen, J. H. (Jan Hendrik) (London [England] : Hart Publishing, 2022)
"... a highly valuable contribution to the legal literature. It adopts a useful, modern approach to teaching the young generation of lawyers how to deal with the increasing internationalisation of law. It is also helpful to the practising lawyer and to legislators." ( Uniform Law Review/Revue de Droit Uniforme ) Volume 4 of this new edition deals with movable and intangible property law. The book addresses the transformation of the models of movable property in commercial and financial transactions between professionals in the international flow of goods, services, money, information, and technology. In this transnational legal order, the emphasis in the new law merchant or modern lex mercatoria of movable property turns to risk management, asset liquidity, and transactional and payment finality. Particular attention is given to the notion of assets and asset classes, the inclusion of monetary claims, the transformation of assets in production and distribution chains, and the type of user, income and enjoyment rights that can be established in them, when they become proprietary, what that means, the role of party autonomy in the creation and operation of these rights, and how they are handled between professional participants and upon a sale to consumers. The volume compares common law and civil law concepts - the one being geared to improving value, the other to consumption; it then identifies their relevance especially in modern finance, and concludes by indicating future directions. The complete set in this magisterial work is made up of 6 volumes. Used independently, each volume allows the reader to delve into a particular topic. Alternatively, all volumes can be read together for a comprehensive overview of transnational comparative commercial, financial and trade law."--
1. Ownership, Possession and Limited, Future, Conditional or Temporary Proprietary Rights in Chattels and Intangible Assets 1.1 Introduction 1.2 The Types of Proprietary Rights in Civil Law 1.3 The Types of Proprietary Rights in Common Law: The Practical Differences from Civil Law. Modern Functional Theories 1.4 Transfer of Proprietary Rights in Chattels in Civil and Common Law 1.5 Proprietary Rights in Intangible Assets in Civil and Common Law 1.6 Trusts. Constructive and Resulting Trusts, Tracking and Tracing. Agency. The Civil Law Response 1.7 Secured Transactions and Conditional or Finance Sales. Floating Charges 1.8 Private International Law Aspects of Chattels 1.9 Private International Law Aspects of Assignments 1.10 The Modern Law of Chattels and Intangibles 1.11 The European Draft Common Frame of Reference 1.12 Uniform or Harmonised Statutory or Treaty Law. The Alternative of Transnationalisation and the Need for and Emergence of a Dynamic Movable Property Law -- 2. Negotiable Documents of Title and Negotiable Instruments 2.1 The Role of Documents 2.2 Negotiable Instruments 2.3 The Dematerialisation of Documents of Title and Negotiable Instruments; Electronic Transfers -- 3. Investment Securities 3.1 The Different Types of Shares and Bonds 3.2 The Transnationalisation of Custodial and Settlement Systems and its Opportunities
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Property; Commercial law; Electronic books